Food Crises and Food Safety Incidents in European Union, United States, and Maghreb Area: Current Risk Communication Strategies and New Approaches. (23rd November 2019) - Chammem, Nadia; Issaoui, Manel; De Almeida, Ana Isabel Dâmaso; Delgado, Amélia Martins
Abstract: Globalization has created a dynamic market, which has dramatically intensified interchanges of goods and information as well as the flow of people among nations. This international phenomenon offers the consumer a choice between a wide variety of foods from diverse locations. However, there are challenges to improving food security and safety on a global scale; the major question is how food safety can be guaranteed while increasing the complexity of food supply chains. A food produced in a certain location usually contains ingredients, additives, and preservatives from different and distant origins. Although countries take several food control measures, their institutional and regulatory frameworks diverge widely, as do the definitions of food crisis, food incidents, and risk management approaches. The present review discusses some past food safety issues and lessons learned. Convergences and differences in the regulatory framework of food control agencies in different regions of the world are herein revealed. Emerging risks are also discussed, particularly the spread of antibiotic resistance in the food chain and the environment, as well as the rise of new antibiotic-resistant pathogenic strains with broader tolerance to environmental factors.